International collaboration meeting between Universiti Teknologi MARA Kelantan Branch (UiTMCK) and Quanzhou Vocational and Technical University, China (QVTU) - UiTM Cawangan Kelantan, Unit Komunikasi Korporat (2022)
The Department of International Affairs (DIA) UiTMCK has organised an international collaboration meeting with Quanzhou Vocational and Technical University, China (QVTU) on 22 November 2022 (Tuesday). The meeting was chaired by Prof. Dr Haji Abdol Samad Nawi, Rector of UiTMCK. It was also participated by the top management of UiTMCK, Assoc. Prof. Ts. Dr Mohd Nasir Ismail, Deputy Rector of Academic Affairs, Encik Farouk Meer Zhar Amir Razli, Deputy Rector of Student Affairs, Dr Syerina Azlin Md Nasir, Deputy Rector of Research, Industrial Linkages & Alumni, UiTMCK as well as the Heads of Faculties of UiTMCK. QVTU was represented by Miss Wu Binru, President of QVTU, Mr. Cai Jinpei, Vice-president of Student Affairs, Mr. Zhang Jianjun, Vice-president of Academic Affairs, Miss Yao Dan, Vice-president of International Affairs, Guo Feifei,Vice-president of Research, Industrial Linkages, Miss Tea Wong, Vice-Director of International Affairs Office and Deans of Faculty.